2019
DOI: 10.56093/ijans.v89i4.89138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of azolla supplementation in feed on semen freezability in bucks

Abstract: The present study was conducted to evaluate the effect of azolla supplementation on semen freezability in Barbari bucks. Ten adult Barbari bucks (2–4 years old) were selected, and divided into control and treatment group (5 bucks in each group) as per completely randomized design. Bucks of control group were fed with 400 g concentrate pellet/day along with 6–7 h grazing while bucks of treatment group were supplemented with 100 g fresh azolla along with 400 g concentrate pellet and 6–7 h grazing. Semen ej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…The possible reason for libido enhancement in the supplemented groups may be attributed to the elevated levels of Zn and Cu present in SP, which are also detected in Azolla, as reported by Chetna and Ravindra [28] as well as Gupta and Chandra [29]. Another study conducted by [30] investigated the effect of zinc in bulls and concluded that zinc deficiency led to poor semen quality and reduced testicular size and libido.…”
Section: Discussionmentioning
confidence: 79%
“…The possible reason for libido enhancement in the supplemented groups may be attributed to the elevated levels of Zn and Cu present in SP, which are also detected in Azolla, as reported by Chetna and Ravindra [28] as well as Gupta and Chandra [29]. Another study conducted by [30] investigated the effect of zinc in bulls and concluded that zinc deficiency led to poor semen quality and reduced testicular size and libido.…”
Section: Discussionmentioning
confidence: 79%
“…1). In our previous study, we found that dietary azolla supplementation signi cantly improves the semen quality and libido in bucks (Gangwar et al, 2019). Earlier study has shown that buck sperm motility was 68.59% after three days of storage at 5℃ (Wen et al, 2019); it reached 78.2% (a signi cant increase) after three days of liquid preservation with Shatavari supplementation.…”
Section: Discussionmentioning
confidence: 83%
“…The semen production data were divided into five periods: I (2001-2004), II (2005II ( -2008, III (2009-2012), IV (2013-2016) and V (2017-2020. Each year was further subdivided into four seasons: winter (December to February), summer (March to April), south-west monsoon (June to August) and north-east monsoon (September to November).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Some studies, including Mukherjee and Bhattacharya (1952), Kodagali (1962), Sinha and Prasad (1966), Tomar et al (1970), Rao and Rao (1975) and Tomar and Gupta (1984), have reported higher initial motility during winter compared to summer, which is consistent with the results of this study. However, there have been conflicting findings, with studies such as Tomar et al (1966), Sinha and Prasad (1966), Mandal et al (2005), Khan et al (2007) and Tiwari et al (2012) reporting no influence of season on initial motility.…”
Section: Initial Motilitymentioning
confidence: 99%